2015
DOI: 10.1097/brs.0000000000000795
|View full text |Cite
|
Sign up to set email alerts
|

Chondrogenic and Fibrotic Process in the Ligamentum Flavum of Patients With Lumbar Spinal Canal Stenosis

Abstract: 5.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
94
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 64 publications
(106 citation statements)
references
References 36 publications
(21 reference statements)
12
94
0
Order By: Relevance
“…The number of comprehensive 'omics' studies to elucidate the molecular pathology of LF degenerative hypertrophy in LSS patients has been increasing 7,14,15) . In these cases, LF samples from LDH patients, for which the age group is often younger than that of patients with LSS, were used as controls.…”
Section: Discussionmentioning
confidence: 99%
“…The number of comprehensive 'omics' studies to elucidate the molecular pathology of LF degenerative hypertrophy in LSS patients has been increasing 7,14,15) . In these cases, LF samples from LDH patients, for which the age group is often younger than that of patients with LSS, were used as controls.…”
Section: Discussionmentioning
confidence: 99%
“…This was already indicated by the pathological findings in LF hypertrophy [3]. However, the underlying pathophysiological mechanisms remain unknown.…”
Section: Introductionmentioning
confidence: 76%
“…According to previous reports [13][14][15], the increased collagen fibers are mainly collagen I and collagen III. As collagen I and collagen III production is believed to strongly correlate with HLF [14,31,32], in our study, we measured collagen I and collagen III expression in LF tissues of the Non-LSS group and LSS group. In the current study, the expression of collagen I and collagen III in LF tissues was found to be increased significantly and was associated with the increases in LF tissue thickness and degree of fibrosis in the LSS group compared with the Non-LSS group.…”
Section: Discussionmentioning
confidence: 99%